2012
DOI: 10.1021/jz2016846
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling a Trap-and-Trigger Mechanism in the pH-Sensitive Self-Assembly of Spider Silk Proteins

Abstract: When the major ampulate spidroins (MaSp1) are called upon to form spider dragline silk, one of nature’s most amazing materials, a small drop in pH must occur. Using a state-of-the-art simulation technique, constant pH molecular dynamics, we discovered a few residues that respond to the pH signal in the dimerization of the N-terminal domain (NTD) of MaSp1 which is an integral step in the fiber assembly. At neutral pH the deprotonation of Glu79 and Glu119 leads to water penetration and structural changes at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 25 publications
5
52
1
Order By: Relevance
“…K65 and R60 are not expected to have pK a values close to the monomer-dimer transition point but are predicted to stabilize the dimer by salt-bridge formation between the subunits 20 . An interaction between K65-D40 was observed in most NMR conformers at pH 5.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…K65 and R60 are not expected to have pK a values close to the monomer-dimer transition point but are predicted to stabilize the dimer by salt-bridge formation between the subunits 20 . An interaction between K65-D40 was observed in most NMR conformers at pH 5.5.…”
Section: Resultsmentioning
confidence: 99%
“…However, NT E79Q and NT E84Q dimerized at low pH, although to a limited extent for the latter 15 . A molecular dynamics simulation predicted the pK a values of all ionizable side chains upon dissociation of dimers into monomers 20 . Here E79 and E119 were identified as the only residues with pK a in the relevant pH range.…”
mentioning
confidence: 99%
“…[47][48][49] Recent studies have shown that CPHMD is a reliable and robust method that is capable of predicting pK a values in a variety of biomolecular systems. [50][51][52][53][54][55][56] Thus, to uncover the pHdependent residues in the CIRV p19 protein involved in siRNA binding stability, we have carried out CPHMD simulations [44][45][46] of the p19 protein dimer in both holo (siRNA-bound) and apo (siRNAfree) forms and determined the pK a values for all titratable residues. These results were then used to calculate the pH-dependent siRNA binding stability profile and corresponding pH-dissociation constant profile.…”
Section: Introductionmentioning
confidence: 99%
“…This was the beginning of a new era of CpH simulation methods still under intense development for biological systems (Baptista et al 1997;Wallace and Shen 2012;Dashti et al 2012;Goh et al 2013a;Chen et al 2013Chen et al , 2014Chen and Roux 2015;Socher and Stich 2016;Donnini et al 2016). Several new simulation schemes that allow pH-coupled MD have emerged following either the Baptista's hybrid MD/PB approach (Baptista et al 1997) or are rooted in the "λ"'s dynamics method (Kong and Brooks 1996).…”
Section: Other Common Constant Ph Simulation Methodsmentioning
confidence: 99%
“…With the increase of computer power, it became doable to replace the implicit solvent model by full atomistic representations (Wallace and Shen 2012;Dashti et al 2012;Chen et al 2013Chen et al , 2014Goh et al 2013a, b;Lee et al 2015Lee et al , 2016Donnini et al 2016). Brooks's lab was the first to extend the CpH MD to nucleic acids in explicit TIP3P water molecules (Goh et al 2013a, b).…”
Section: Other Common Constant Ph Simulation Methodsmentioning
confidence: 99%